OPTIMATION OF ANTIMICROBIAL SUBSTANCE PRODUCTION IN CELL FREE EXTRACT FROM THERMOPHYLIC BACTERIA FERMENTATION AFTER MERAPI ERRUPTION - Evy Yulianti; Anna Rakhmawati; Kartika Ratna Pertiwi (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
The aims of this study was to investigate the effect of medium with different pH (6,7,9), salt concentration (0,5; 1; 2 %) and fermentation periode (24 and 48 hr) to the antimicrobial activity of cell free extract to three pathogens, Eschericia coli, Staphylococcus aureus, and Candida albican. This study consists of antimicrobial compounds production with different medium and continued by antimicrobial tested to fungi and bacterial pathogens Eschericia coli, Staphylococcus aureus, and Candida albican by Kirby Bauer method with paper disk. Different salt concentration, pH and fermentation periode affected the antimicrobial activity potency of cell free extract yielded by thermophylic bacteria. Treatment which yielded CFE with the best antimicrobial activity was treatment with 24 hr fermentation, pH 7 and salt concentration 2% to S aureus and pH 6 salt concentration 1% to E coli. Cell free extract had no potency as antifungi to Candida albicans except CFE yielded by thermophylic bacteria fermented in medium with pH 7 and salt concentration 1% in 24 hr with inhibition zone index 1,17. Keywords: cell free extract, antimicrobial, pH, salt concentration, fermentation period